Diamond growth on metals - Qi Hua Fan,
This work studies diamond growth on copper by microwave plasma chemicalvapour- deposition (MPCVD). Diamond nucleation and growth characteristics are the essential aspects in CVD process. We show that the substrate pre-treatment influences strongly the diamond nucleation. The diamond quality and growth characteristics are mainly controlled by the deposition conditions. In practical applications CVD diamonds fall into two main forms. One is freestanding films and another is adherent coatings on different materials. Copper is a promising substrate material for preparing free-standing diamond films because of its non-carbon affinity. However, the large mismatch in thermal expansion between the diamond and copper usually leads to the film cracking during the post cooling procedure. In order to overcome this problem we develop a two-step growth method which consists of two growth stages. In the first stage a short deposition is performed for obtaining a sufficient but non-continuous nucleation. Then a quick ramp down in plasma power and temperature releases the diamond crystals from their trapped positions. In the second stage a normal deposition is performed for obtaining continuous diamond films of desired quality. No cracking in the film happens during the post cooling procedure after the second deposition. On the other hand, many applications require sufficient adhesion of diamond coating to the substrate. Since direct deposition of diamond on copper yields no adhesion, we propose using an interlayer which can provide adequate adhesion to both the copper substrate and the diamond film. The diffusion behaviour of carbon and copper in different refractory materials as well as their carbide bond strength is considered in order to find a suitable interlayer material. It is shown that titanium is one of the promising candidates. Adherent diamond coatings on copper are obtained using a titanium buffer layer of 0.2-5 pm thick. The electrical conductivity of the diamond films show a strong and controllable dependence on the deposition conditions. Selective deposition of diamond on the Tilcopper are demonstrated. In addition, adherent diamond coating on steel is also obtained by using a titanium interlayer. Quantitative evaluation of the adhesion of diamond coatings is a fundamental subject and has been a long standing concern in various of coatings. We show that conventional methods, like adhesion scratch tests, pull-off tests, indentation tests, and micro-Raman spectroscopy, usually can not give quantitative results when examining the diamond coatings. Therefore, we develop two new methods, trying to solve this problem. The first one is a thermal quench combined with micro-Raman spectroscopy method and the second is a micro-indentation test based model. In the thermal quench method the diamond coatings on TiICu substrate are quenched from room temperature to lower temperatures. The critical temperature at which the film detaches is revealed by the shift of the diamond Raman line to the stress-free value of 1332 cm-'. The coating adhesion is considered to be equivalent to the thermal stress induced by the quench and can be quantitatively calculated from the thermal and mechanical properties of the substrate and the diamond. For the diamond coatings on Tilcopper, this method reveals an adherence of approx. 2.42 GPa. The micro-indentation model is based on the experimental evidence that small indentation load always causes round spallation in the diamond films whatever the shape of the indenter is. An exponential sink-in deformation of the coating under the indentation is proposed (y = -a;bexp(-bx)). The deformation stress at the spallation edge is considered the coating adhesion. The modeled adhesion of the diamond coatings on copper is about 1.921-1.956 GPa, which is in agreement with the thermal quench results. The validity of this model is also verified by its self-consistence. Residual stress is an essential aspect determining the reliability of diamond coatings. We find experimentally that the increase in the film thickness leads to a shift of the diamond Rarnan line from higher wave numbers to 1332 cm-'. A linear relationship between the film thickness and the in-plane stress is observed and a theoretical model is developed to interpret the results. This decrease in stress along the film thickness is usually not taken into account in other stress measurement techniques, like substrate curvature, X-ray diffraction etc. The most important mechanical properties, namely the hardness and wear resistance, of the diamond coatings on copper are investigated. The coating hardness is modeled by considering the coatinglsubstrate a composite material. Tribological tests show a high wear resistance of the diamond coatings. The friction coefficient is found to be proportional to both the wear load and the diamond grain size.